2021
DOI: 10.3389/fimmu.2021.767347
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Exacerbates COVID-19 Pathology Through Activation of the Complement and Kinin Systems

Abstract: Infection with SARS-CoV-2 triggers the simultaneous activation of innate inflammatory pathways including the complement system and the kallikrein-kinin system (KKS) generating in the process potent vasoactive peptides that contribute to severe acute respiratory syndrome (SARS) and multi-organ failure. The genome of SARS-CoV-2 encodes four major structural proteins – the spike (S) protein, nucleocapsid (N) protein, membrane (M) protein, and the envelope (E) protein. However, the role of these proteins in either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Strikingly, our proteomics data revealed extensive upregulation of kallikrein proteins in the oral lavage of SARS-CoV-2 POS mice. Savitt et al recently reported direct interaction and activation of the kallikrein/kinin system (KKS) by recombinant SARS-CoV-2 proteins S, M, N, and E [ 44 ]. High molecular weight kininogen (HK) and plasma prekallikrein (PK) bring about the sequelae of bradykinin, and complexing of HK/PK with blood coagulation factor XII (FXII), initiate the intrinsic clotting cascade with the aid of misfolded proteins and polyphosphate [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, our proteomics data revealed extensive upregulation of kallikrein proteins in the oral lavage of SARS-CoV-2 POS mice. Savitt et al recently reported direct interaction and activation of the kallikrein/kinin system (KKS) by recombinant SARS-CoV-2 proteins S, M, N, and E [ 44 ]. High molecular weight kininogen (HK) and plasma prekallikrein (PK) bring about the sequelae of bradykinin, and complexing of HK/PK with blood coagulation factor XII (FXII), initiate the intrinsic clotting cascade with the aid of misfolded proteins and polyphosphate [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though complement was not tested and abnormalities could not be excluded at that time, eculizumab, a C5 inhibitor, was administered. Furthermore, it has been suggested that a blockade of C5a may be crucial for inhibition of the cytokine storm ( 30 , 31 ). Up to date, none of the viruses implicated as possible triggers of myositis have been shown to directly infect muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The virus itself has been shown to bind MBL, Ficolin-2 and Collectin-11, via its S- and N-proteins, with subsequent LP-mediated C3b and C4b deposition ( 44 , 45 ). Structural parts of the virus have also been shown to bind C1q and trigger complement activation ( 43 ). COVID-19 is strongly associated with ischemic cells, apoptosis, and cell death ( 15 , 20 , 40 ), initially occurring in the lung tissue.…”
Section: Activation Individual Components Of Iiis In Covid-19mentioning
confidence: 99%
“…Multiple proinflammatory cytokines and chemokines such as TNF, IL-1b, IL-6, and MCP-1 are produced in response to C3a and C5a generation that further amplifies the production of acute-phase proteins (41,42). The IIIS activation is multifactorial: The virus itself can activate the IIIS directly via the CP and LP of the complement system and via the KK system (43)(44)(45). Another likely activation mechanism is tissue damage in the lungs with apoptotic and necrotic cells that initiates the overactivation of IIIS in its function to eliminate cells or cell debris (46).…”
Section: Activation Individual Components Of Iiis In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation